Use of RE-AIM to address health inequities: Application in a low-income community health center-based weight loss and hypertension self-management program - Glasgow, Russell E (Springer-Verlag, 2013)
While health inequities are well documented, and there are helpful frameworks to understand health disparities, implementation frameworks are also needed to focus the design, evaluation, and reporting on interventions targeting populations at increased risk. This study aims to describe how the reach, effectiveness, adoption, implementation, and maintenance (RE-AIM) framework can be used for these purposes and illustrate its application in the context of a randomized, pragmatic weight loss and hypertension self-management intervention. RE-AIM was used to both plan and evaluate the Be Fit Be Well program for urban community health center patients. The RE-AIM framework helped to focus attention on and produce high rates of adoption and reach. Implementation rates varied across components. Weight losses were statistically significant, but not clinically significant. They were robust across a variety of patient characteristics, and the program was relatively of low cost. Individual weight losses and blood pressure reductions were maintained throughout the 24-month period, but the program was not sustained at any of the three settings. Implementation frameworks such as RE-AIM can help design pragmatic interventions that focus on both the context for disparities reduction and the ultimate goal of public health impact.